A Cry in the Dark - Kumar, Haobam Paban (India : Oli Pictures, 2006)
In India’s eastern state of Manipur, a young woman was arrested in 2004 on the pretext of being an insurgent, then reportedly raped and killed in police custody. She was a village girl of no particular prominence but the popular movement that rose up in the wake of Thangiam Manorama’s death shook the foundations of the government. The film captures the showdowns between unarmed protesters and the officers of the Assam Rifles.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films